STRATEGI ACCOUNT PAYABLE DALAM MELAKUKAN PEMBAYARAN KEPADA SUPPLIER SELAMA PANDEMI COVID-19 DI SWISS-BELHOTEL RAINFOREST KUTA BALI - Putu Dessy Wulandari; A.A.Nym.Sri Wahyuni; Victor Bangun Mulia (Jurusan Pariwisata Politeknik Negeri Kupang, 2023)
Hotels are one of the tourism sectors affected by the pandemic. The aim of the research is to analyze the strategy of the account payable section in making payments to suppliers and its impact during the co-19 pandemic at Swiss- Belhotel Rainforest. The theory used is the Eisenhower Decision Matrix theory and qualitative research methods. The results of the study, there are four Swiss-Belhotel Rainforest account payable strategies in making payments to suppliers; 1) Mapping operational needs, 2) Making a list of payments 3) Flexible payments, 4) Negotiating with suppliers. The positive impact of the strategy used is that the hotel continues to survive because the fulfillment of operational needs can still be carried out. The negative impact is that some problems arise such as missing notes and the process of filing by accounts payable is slightly delayed due to incomplete supporting files.